Organoleptic Characteristics of Instant Uduk Rice with Different Types of Rice Varieties and Steaming Time - Pramesthi, Azzahra Nur Shifa; Ratna Yulistiani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Instant uduk rice is a quick-cooking rice that can be prepared within 3-5 minutes and is characterized by porous rice grains. Different types of rice varieties and the gelatinization process during steaming are known to affect the organoleptic properties of instant uduk rice. The purpose of this study was to determine the effect of different types of rice varieties and steaming time on the physicochemical and organoleptic characteristics of instant uduk rice. This research method used a completely randomized design (CRD) factorial pattern of 2 factors with 2 replications. Factor I was rice variety (IR 42, IR 64, and Sintanur) and factor II was steaming time (20, 30, 40 minutes). Organoleptic testing in this study used a scoring test. The data obtained will be analyzed using Analysis of Variance (ANOVA). The results showed that different varieties of rice and steaming time affected the organoleptic properties of instant uduk rice.